Complementary and alternative medicine : containing and expanding therapeutic possibilities - Dew, Kevin (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Complementary and Alternative Medicine is a sociological investigation of CAM in contemporary society, and an exploration of the forces throughout the globe, across different institutions, and within different therapeutic spaces, that constrain or foster alternative medicine. Drawing on 30 years of research, the book identifies the trends in the use of CAM and explores the scientific, political and social challenges that CAM faces in relation to orthodox medicine. The author examines the varieties of CAM practices and how they manifest in different institutional spaces - including public inquiries, the orthodox medical practitioner's consulting room, medical journals and the homes of those who use CAM. It also compares unorthodox practices in different geo-political settings, namely the global north and the global south. This book is valuable reading for higher-level undergraduate and postgraduate social science students, including those in psychology, sociology, anthropology, health sciences, and related disciplines. It is relevant for courses in medical sociology, medical anthropology and social science and health, and a broader audience interested in contemporary health issues, controversies and alternative medicine"--
OCLC-licensed vendor bibliographic record.
Keywords: Alternative medicine; Traditional medicine; HEALTH & FITNESS / Alternative Therapies; PSYCHOLOGY / Applied Psychology; BODY, MIND & SPIRIT / Healing / General